Manual de programación del mantenimiento electromecánico preventivo de un vehículo liviano para el sector automotriz. - Pérez Contreras, José Carlos (Universidad Antonio Nariño, 2023)
The idea of ​​this project arises from the need to maintain tools, equipment, materials and devices in optimal conditions for better performance during maintenance and thus not have unforeseen events and/or failures to the time to use them. This allows us to enter the study of the electromechanical maintenance of a light vehicle in the automotive sector, since it is expected to achieve optimum performance, since they are an important asset for the transportation and industry. Likewise, scheduling maintenance electromechanical of a light vehicle will allow to show detail how these procedures are performed, so that so that the vehicle can be kept in optimal conditions during its useful life. They will be explained in the same way the verification processes of each of the pieces of the existing light vehicles in the automotive sector.